What Is a House? Exploring the Relationship Between Housing and Economic Development (Global Journal of Human-Social Science, 2024)
The debate on the hypothesis that massive housing construction is the starting point of economic development has been ongoing since the end of World War II Proponents of this hypothesis believe that housing serves as an impetus for economic development and there is practical evidence to support this view Opponents however state that housing is not a cause but a consequence of development This latter group in line with mainstream economic models considers housing as a private consumer good such as automobile clothing food and furniture While the supply of housing entails enormous economies of scale the consumption gives rise to interdependence costs To internalize these costs economic goods associated with interdependence costs require group or political consideration Thus it becomes inappropriate to model a house as a consumer good The purpose of this article is to show that physical structure alone does not constitute a house Private and public goods complementary to housing which lead to scale economies and elimination of interdependence costs excluded from relevant housing models produce inadequate definition of a house If these public goods complementary to housing are the stimuli needed for sustainable economic development and growth then the debate should be about the definition of a house-is a house an economic consumer product or a political good
Keywords: public services; publicly provided private goods; housing demand; economic development